The level of physical fitness and movement compatibility associated with health and activity patterns among middle school students - Lamiaa Abdul-Sattar Dr. Widad Kadhum (الرياضة المعاصرة)
the importance of the research emerged in the role of the level of physical fitness and motor coordination in health and activity for female students in the intermediate stage . As for the research problem, lies in the fact that some male or female teachers in the field of sports do not resort to exercising fitness and using modern and advanced exercises that may help them to maintain their health , As the two researchers resorted to using exercises related to fitness and motor coordination in order for the students to enjoy health and to practice the activity at the best level. The research aims to identify the level of physical fitness and movement-related movement related to health and patterns of activity in female students in the intermediate stage. As for the hypothesis of the research, it is found that there are significant differences between the pre and post tests in the level of fitness, motor compatibility related to health, and patterns of activity in the two research groups.The two researchers used the experimental approach with the two equal and controlling and experimental groups. The research sample consisted of middle school students, whose number reached (34) female students. And patterns of activity for middle school studentsThe researchers recommend the need to use various and targeted exercises related to physical fitness and motor alignment in order to maintain the health of the body as well as the practice of activities in a natural way, and the need to pay attention to conducting tests related to physical fitness and periodic motor alignment in order to know the level of fitness and compatibility of students and develop them.